A Process‐Model Perspective on Recent Changes in the Carbon Cycle of North America. Issue 9 (9th September 2022) - Murray‐Tortarolo, Guillermo; Poulter, Benjamin; Vargas, Rodrigo; Hayes, Daniel; Michalak, Anna M.; Williams, Christopher; Windham‐Myers, Lisamarie; Wang, Jonathan A.; Wickland, Kimberly P.; Butman, David; Tian, Hanqin; Sitch, Stephen; et al.
Abstract: Continental North America has been found to be a carbon (C) sink over recent decades by multiple studies employing a variety of estimation approaches. However, several key questions and uncertainties remain with these assessments. Here we used results from an ensemble of 19 state‐of‐the‐art dynamic global vegetation models from the TRENDYv9 project to improve these estimates and study the drivers of its interannual variability. Our results show that North America has been a C sink with a magnitude of 0.37 ± 0.38 (mean and one standard deviation) PgC year −1 for the period 2000–2019 (0.31 and 0.44 PgC year −1 in each decade); split into 0.18 ± 0.12 PgC year −1 in Canada (0.15 and 0.20), 0.16 ± 0.17 in the United States (0.14 and 0.17), 0.02 ± 0.05 PgC year −1 in Mexico (0.02 and 0.02) and 0.01 ± 0.02 in Central America and the Caribbean (0.01 and 0.01). About 57% of the new C assimilated by terrestrial ecosystems is allocated into vegetation, 30% into soils, and 13% into litter. Losses of C due to fire account for 41% of the interannual variability of the mean net biome productivity for all North America in the model ensemble. Finally, we show that drought years (e.g., 2002) have the potential to shift the region to a small net C source in the simulations (−0.02 ± 0.46 PgC year −1 ). Our results highlight the importance of identifying the major drivers of the interannual variability of the continental‐scale land C cycle along with the spatial distribution of local sink‐source dynamics. Plain Language Summary: In recent decades terrestrial ecosystems in North America have absorbed more carbon (C) from the atmosphere than they have released, thus acting as a net land C sink. Nonetheless, several gaps remain in our understanding of how the newly assimilated C is partitioned among the various components of the land ecosystem, and about the impact of recent fires and extreme climatic events on the C stored in vegetation and the soil. In this study, we employed 19 state‐of‐the‐art global dynamic vegetation models to advance our understanding of the land C dynamics over North America over the period 2000–2019. Our results suggest that 57% of the newly assimilated C over this period went into the vegetation, 30% to the soils, and the rest as litter. These new land C gains were found mostly over the temperate and boreal forest regions, which together accounted for 81% of the entire North American sink. Finally, we show that fire and drought are closely related to the year‐to‐year variability of the sink magnitude, and during extreme conditions (e.g., during 2002) they have the potential to reverse the land into a C source to the atmosphere. Key Points: Land C sink dynamics for North America were evaluated using 19 state‐of‐the‐art Dynamic Global Vegetation Models during 2000–2019 North America has been a net C sink with a magnitude of 0.37 ± 0.38 PgC year −1 and an increasing trend over time We identify different spatial and temporal drivers of the variability in land C fluxes across the region, including fire and drought